MXene Enables Stable Solid‐Electrolyte Interphase for Si@MXene Composite with Enhanced Cycling Stability. Issue 16 (17th August 2021) - Zhou, Hao; Cui, Cong; Cheng, Renfei; Yang, Jinxing; Wang, Xiaohui
Abstract: Silicon (Si) has been gaining considerable attention in the field of Li‐ion batteries although unstable solid‐electrolyte interphase (SEI), extreme volume changes and inferior conductivity hinder its practical application. Herein, ultrasonic‐assisted electrostatic self‐assembly of fluidic colloidal coprecipitation of MXene wrapped Si nanoparticles (Si@MXene) is proposed. Utilizing the natural negatively charged MXene to capture positive‐charged Si nanoparticles, the homogeneous Ti3 C2 Tx MXene coating on Si nanoparticles prevents the nanoparticles from directly contacting the electrolyte and thus enables the formation of a stable SEI film on the composite particulates. Due to the elimination of unstable solid‐electrolyte interphase on the surface of Si nanoparticles, Si@MXene delivers high capacity and excellent retention stability of 94 % after 100 cycles. The strategy demonstrated here offers the rational design of MXene‐coated Si anodes with high capacity and superior cycling stability. Abstract : Few‐layers of Ti3 C2 T x MXene coating enables excellent cycling stability of silicon anode by suppressing the formation of unstable solid‐electrolyte interphase film on the surface of silicon nanoparticles.